Collaboration between traditional and central authorities in chieftaincy succession conflicts management in Ghana: Evidence from Bole traditional area - Tseer, Tobias; Sulemana, Mohammed (Frontiers in Human Dynamics, 2022)
Chieftaincy succession conflicts are a near ubiquitous phenomenon in Ghanaian Chiefdoms. While many studies have investigated the causes and implications of such conflicts, the extent to which traditional and central authorities collaborate in the management of chieftaincy succession conflicts in Ghana is largely understudied. This is the gap in literature that this study attempted to fill. The study was situated within the frameworks of the Collaborative Leadership Theory. The triangulated variant of the Mixed Method Approach was adopted for the study where fourteen Key Informants were recruited using Expert Purposive Sampling technique and 99 others recruited for a survey using Stratified and Simple Random Sampling Techniques. The unit of analysis was the Bole chieftaincy succession conflict management team. Data was solicited around the level of representation of traditional and central authorities on the team, the roles assigned to each member, levels of commitment of each member and the significance of the roles played by each member at the various stages of conflict management. The analysis of the data revealed that there were some levels of collaboration at the initial stages of the conflict but less so at the level of implementation and nothing was done at all at the stages of assessing the impact of the implementation and carving pathways for future peace. The study, therefore recommended that the state, through the National Security Council may liaise with the National House of Chiefs to fashion out better ways of collaborating in conflict management, from the initial stages to the final stages, so as to completely resolve chieftaincy conflicts which are often disruptive and destructive.